1986
DOI: 10.1111/j.1365-3083.1986.tb02177.x
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte Activation and Induction of Interferon Gamma in Human Leucocyte Cultures by the Mitogen in Mycoplasma arthritidis Supernatant (MAS)

Abstract: This report succinctly summarizes a number of experiments in which human leucocytes were activated by the mitogen in the supernatant of cultured Mycoplasma arthritidis (MAS). Lymphocytes from a large number of donors were found to be reactive when the two parameters of lymphoproliferation and of production of gamma interferon were analysed. Lymphocytes of cord blood origin were also reactive in lymphoproliferation. Their interferon production was low, but this has been established previously for mitogens in ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…However, the release of large amounts of Iymphokines by the activated cells (148)(149)(150), and the swamping out of directed responses by the overwhelming T-cell proliferation could contribute to an immunosuppressive state and favor the bacteria. However, the release of large amounts of Iymphokines by the activated cells (148)(149)(150), and the swamping out of directed responses by the overwhelming T-cell proliferation could contribute to an immunosuppressive state and favor the bacteria.…”
Section: Some Evolutionary Speculationmentioning
confidence: 99%
“…However, the release of large amounts of Iymphokines by the activated cells (148)(149)(150), and the swamping out of directed responses by the overwhelming T-cell proliferation could contribute to an immunosuppressive state and favor the bacteria. However, the release of large amounts of Iymphokines by the activated cells (148)(149)(150), and the swamping out of directed responses by the overwhelming T-cell proliferation could contribute to an immunosuppressive state and favor the bacteria.…”
Section: Some Evolutionary Speculationmentioning
confidence: 99%
“…Furthermore, mycoplasma-derived products can also induce proinflammatory cytokine production. Human monocytes can be triggered by a soluble entity, isolated from Mycoplasma arthritidis culture supernatant (4), that has been shown to be a basic protein of 20 to 25 kDa (15). Mycoplasma fermentans-derived high-molecular-weight material with a molecular mass of over 1.5 x 106 Da induces IL-6 production by human monocytes; this activity requires previous culture of mycoplasma with eucaryotic cells or extracts (19).…”
mentioning
confidence: 99%
“…M. arthritidis has been the subject of extensive studies and was shown to act as a mitogen for lymphocytes from mice, rat and human , 1986a, 1986b, Kirchner et al 1986a. The induction of murine T-cell proliferation and cytotoxic activity by M. arthritidis is MHC class II1-E antigen-restricted (BekofT et al 1987).…”
Section: Mycoplasma Effects On T Lymphocytes In Vitromentioning
confidence: 99%
“…The production of interferon-y by murine spleen cells upon stimulation by M. arthritidis is restricted to the I-E/I-C subregion of the MHC, as it is for lymphocyte proliferation and induction of cytotoxic lymphocytes (Cole & Thorpe 1984). MAS also induces production of IFNy in human leukocyte cultures (Kirchner et aL 1986a).…”
Section: Mycoplasma-induced Production Of Cytokinesmentioning
confidence: 99%